El pez volador : antología de cuentos - Navarro, Hipólito G. (Hipólito González), 1961-; Sáez de Ibarra, Javier (Madrid : Editorial Páginas de Espuma, 2016)
Anthology of 20 short stories.
Premio El Público de narrativa, 2008
Online resource; title from ePub title page (Digitalia, viewed February 10, 2018)
Keywords: Short stories; Electronic books